Imprints of the Little Ice Age and the severe earthquake of AD 2001 on the aquatic ecosystem of a tropical maar lake in El Salvador. (October 2022) - Wojewódka-Przybył, Marta; Krahn, Kim J; Hamerlík, Ladislav; Macario-González, Laura; Cohuo, Sergio; Charqueño-Celis, Fernanda; Cisneros, Anaís; Hoelzmann, Philipp; Yang, Handong; Rose, Neil L; Zawisza, Edyta; Pérez, Liseth; et al.
Using a 530-year sediment record from the maar Lake Apastepeque, El Salvador, and based on diverse geochemical and biological (cladocerans, chironomids, diatoms, ostracods, testate amoebae) indicators, we estimated climatic and environmental alterations during the Little Ice Age (LIA) and reconstructed the recent history of the lake. Results demonstrate relatively humid conditions in the mid-elevations (500 m a.s.l.) of El Salvador during most parts of the LIA, resulting in high lake levels. Contrarily, the first part of the LIA was characterized by drier climates comparable to studies from Mexico and Belize, which correlated this phase with the Spörer minimum. Regional comparison with palaeorecords from the northern Neotropics reveals a high heterogeneity in local expressions of the LIA in Central America, likely connected to the high topographic heterogeneity of the region. Since the beginning of the 20 th century, Lake Apastepeque has experienced enhanced human impact expressed as increased nutrient supply. The most recent period was characterized by significant environmental disturbance, which we relate to an upper-crustal earthquake, one of the strongest over the last 500 years, that affected the region on 13 th February 2001 (Mw = 6.6, epicentre at 10 km depth, 30 km from the lake). The release of toxic bottom components such as hydrogen sulphide and high turbidity and turbulence of water caused major species turnover in the lake ecosystem, resulting in a massive fish kill and colonization by large cladocerans. Modern sediments still show slightly altered biota communities compared to pre-earthquake assemblages, indicating that the ecosystem has still not fully recovered.